O tornar-se mãe em meio à pandemia do Covid-19 e a rede de apoio para a maternidade - Rosa, Karen Sihe Lima da (2023)
The experience of transition to motherhood is presented as a specific phase of the psycho-affective development of the woman who becomes a mother, and involves profound changes in identifications. When considering the social withdrawal that occurred during the covid-19 pandemic, the present study highlights the relevance of such deprivation for women who experienced the transition to motherhood, this unique and significant moment in their lives, during this period. From this, the present exploratory qualitative study aimed to understand the experience of women in becoming mothers during the Covid-19 pandemic, as well as to identify the support network of women in this context. Five women participated, who became mothers in the midst of the Covid-19 pandemic, between March and August 2020, in a city in the interior of the state of Rio Grande do Sul. Data collected through a sociodemographic questionnaire, an interview about the Transition of Motherhood During the Pandemic and the Network Map were submitted to Content Analysis. The results were presented in the format of two scientific articles: “Maternity construction: becoming a mother of the first child in the context of the Covid-19 pandemic.” and “The support network in the transition to motherhood during the pandemic: accessibility and availability”. Loneliness, exhaustion, anxieties, anxieties, doubts and fears were identified as feelings and sensations that were part of the experience of becoming a mother in the study participants. Predominantly on issues of breastfeeding and the few hours of sleep. Another propelling point of anguish was the need that the participants felt, for a reconstruction of the identity and the construction of the mother's identity. It is considered relevant to develop interventions aimed at women's health in the process of becoming mothers. There was a female predominance in the participants' bonds. However, the two main links in the network that offered the most support were the partner and the mother's mother. It is considered relevant to improve knowledge about significant personal networks, in order to make it possible to place them even more in the spotlight, taking into account their essential existence and functioning.